2017
DOI: 10.1051/epjconf/201714302071
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the temperature distribution in a minichannel using ANSYS CFX and a procedure based on the Trefftz functions

Abstract: Abstract. This work discusses the mathematical model for laminar-flow heat transfer in a minichannel. The boundary conditions in the form of temperature distributions on the outer sides of the channel walls were determined from experimental data. The data were collected from the experimental stand the essential part of which is a vertical minichannel 1.7 mm deep, 16 mm wide and 180 mm long, asymmetrically heated by a Haynes-230 alloy plate. Infrared thermography allowed determining temperature changes on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The authors of this work continue their experimental and theoretical investigations, testing the application of analytical [2], semi-analytical-numerical methods with the application of the Trefftz functions [21][22][23][24] and several commercial numerical programs: Simcenter STAR-CCM+ [14], ADINA [25,26] and ANSYS CFX [27] programs to perform heat transfer calculations during fluid flow in mini-channels.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this work continue their experimental and theoretical investigations, testing the application of analytical [2], semi-analytical-numerical methods with the application of the Trefftz functions [21][22][23][24] and several commercial numerical programs: Simcenter STAR-CCM+ [14], ADINA [25,26] and ANSYS CFX [27] programs to perform heat transfer calculations during fluid flow in mini-channels.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications to the configuration of the inlet manifold channel and plenum were carried out to improve the fluid distribution. The first attempts at numerical calculations according to the mathematical model describing heat transfer during fluid laminar flow in minichannels using ANSYS CFX program and ADINA software, and the computations based on the finite element method and the Trefftz functions were performed by the authors of this work and shown in [29,30], respectively. The outcomes of the comparative analysis were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experimental data, analytical and analytical-numerical methods using the Trefftz functions, the heat transfer coefficient values on the heating surface contacting the fluid flowing in a minichannel were determined. Only the first attempts have been made to predict the behavior of cooling fluids flowing in minichannels due to numerical calculations using ANSYS CFX [30] and ADINA software [29].…”
Section: Introductionmentioning
confidence: 99%
“…The heat transfer issues can be modelled by numerically method using specialized software such as ANSYS CFX and Fluent like in [19,20].…”
Section: Introductionmentioning
confidence: 99%